Desain Alat Pencacah Sampah Organik Berkapasitas 40 Kg/Jam - ., Wilarso; Domodite, Aswin; Sholih, Hilman; Indrawan, Rudi; Ramdani, Fauzi (Fakultas Teknik UMSU, 2022)
To improve the quality of fish livestock, bait that has the nutrients needed is needed. However, the obstacles experienced by farmers are getting their feed that does not meet the criteria, and in the process, they still use manual tools. The purpose of this research is to design an organic waste chopper with a capacity of 40 Kg/minute for the needs of making compost and eating maggots (black flies). The method in the research conducted using solid work to determine the shape, size, and working system of the tool. The method in this study is the design of an organic waste chopper with a capacity of 40 kg/minute. The results of this study are the design of an organic waste chopper with a capacity of 40 kg/minute to reduce organic waste and can be used as organic compost, liquid compost, or black fly bait media for fish feed. The calculation is that the electric motor shaft torque is 79 Nm, with a tensile stress of 33.6 N/m2. Meanwhile, in the calculation of the capacity obtained as follows; 1. Calculation of the capacity of the counter Q = 667 grams/minute. 2. Planned blade rotation 5,929 rev/min. 3. Motor power 1500 Watt, 4. Tensile voltage 33.6 N/m2. 5) Calculation of cutting capacity 2.025 gram/min. Based on the initial design of this chopper, it is 40 Kg/hour